The adoption and use of collaboration information technologies: International comparisons - Bajwa, D.; Lewis, L.; Pervan, Graham; Lai, V. (Palgrave Macmillan, 2005)
Information technology (IT) applications to support group decision processes have been of considerable interest over the years. With the emergence of virtual team arrangements and the advent of emerging information and networking technologies, an increasing amount of attention is now being aimed at understanding collaboration among group members, as they make decisions to accomplish tasks. Effective and efficient collaboration is critical from a decision quality and decision timeliness standpoint. Commonly known as collaborative information technologies (CITs), many technology solutions have the capability to enhance collaboration and facilitate group decisions in task accomplishment by enabling better communication, sharing of information, ideas, expertise and evaluating alternatives, irrespective of time and distance barriers. Many studies have investigated such individual CIT solutions in different regional settings. However, despite the fact that no single medium can support collaboration in different types of tasks, there is a scarcity of research investigating the adoption and use of mutiple CIT options across regions. This paper builds upon innovation diffusion theory and tests a research model to validate five antecedents of collective adoption and use of seven CITs in the US, Australia, and Hong Kong. Sub-sample analyses of data collected from 344 organizations in these three regions suggest that not only do adoption and use patterns of some CIT solutions vary across regions but so do the antecedents that explain their proliferation. Implications of our findings are discussed for practitioners and researchers.